Single domain Camelid antibody fragments for molecular imaging and therapy of cancer - Li, Shulin; Hoefnagel, Sanne Johanna Maria; Krishnadath, Kausilia Krishnawatie (Frontiers in Oncology, 2023)
Despite innovations in cancer therapeutics, cancer remains associated with high mortality and is one of biggest health challenges worldwide. Therefore, developing precise cancer imaging and effective treatments is an unmet clinical need. A relatively novel type of therapeutics are heavy chain variable domain antibody fragments (VHHs) derived from llamas. Here, we explored the suitability of VHHs for cancer imaging and therapy through reviewing the existing literature. We searched the MEDLINE, EMBASE and Cochrane databases and identified 32 papers on molecular imaging and 41 papers on therapy that were suitable for comprehensive reviewing. We found that VHHs harbor a higher specificity and affinity compared to mAbs, which contributes to high-quality imaging and less side-effects on healthy cells. The employment of VHHs in cancer imaging showed remarkably shorter times between administration and imaging. Studies showed that 18F and 99mTc are two optimal radionuclides for imaging with VHHs and that site-specific labelling is the optimal conjugation modality for VHHs with radionuclide or fluorescent molecules. We found different solutions for reducing kidney retention and immunogenicity of VHHs. VHHs as anticancer therapeutics have been tested in photodynamic therapy, targeted radionuclide therapy, immunotherapy and molecular targeted therapy. These studies showed that VHHs target unique antigen epitopes, which are distinct from the ones recognized by mAbs. This advantage means that VHHs may be more effective for targeted anticancer therapy and can be combined with mAbs. We found that high cellular internalization and specificity of VHHs contributes to the effectiveness and safety of VHHs as anticancer therapeutics. Two clinical trials have confirmed that VHHs are effective and safe for cancer imaging and therapy. Together, VHHs seem to harbor several advantages compared to mAbs and show potential for application in personalized treatment for cancer patients. VHH-based imaging and therapy are promising options for improving outcomes of cancer patients.